Nonsurgical Interventional Spine Pain Procedures: Outcomes and Complications. Issue 4 (14th April 2023) - Whitaker, Colin D.; Stone, Benjamin K.; Gregorczyk, Jerzy A.; Alsoof, Daniel; Hardacker, Kyle; Diebo, Bassel G.; Daniels, Alan; Basques, Bryce
Abstract : » Nonsurgical interventional spine pain procedures provide an additional treatment option for lower back pain at the traditional bifurcation of conversative vs. operative management. » Transforaminal epidural steroid injections, radiofrequency ablations, intrathecal drug delivery, and spinal cord stimulation were found to be effective and safe techniques when applied to their specific indication. » Thermal annuloplasty and minimally invasive lumbar decompression showed mixed support. » Discography, sacroiliac joint injections, and spinous process spacers lacked sufficient evidence to support efficacy. » Medial branch blocks and facet joint injections were found to be useful diagnostic tools.